2013
DOI: 10.1186/1532-429x-15-5
|View full text |Cite
|
Sign up to set email alerts
|

Incremental value of cardiovascular magnetic resonance over echocardiography in the detection of acute and chronic myocardial infarction

Abstract: BackgroundAlthough echocardiography is used as a first line imaging modality, its accuracy to detect acute and chronic myocardial infarction (MI) in relation to infarct characteristics as assessed with late gadolinium enhancement cardiovascular magnetic resonance (LGE-CMR) is not well described.MethodsOne-hundred-forty-one echocardiograms performed in 88 first acute ST-elevation MI (STEMI) patients, 2 (IQR1-4) days (n = 61) and 102 (IQR92-112) days post-MI (n = 80), were pooled with echocardiograms of 36 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Echocardiography has a high sensitivity but moderate specificity for the diagnosis of acute MI 5. Previous studies have shown that although sensitivity is high, specificity is much poorer 6 7…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography has a high sensitivity but moderate specificity for the diagnosis of acute MI 5. Previous studies have shown that although sensitivity is high, specificity is much poorer 6 7…”
Section: Discussionmentioning
confidence: 99%
“…CMR is invaluable to the study of patients with ischaemic heart disease and has made a major impact on this field and is now widely used to delineate myocardial infarction, [ 161 , 162 ] and scarring, [ 163 ] although more recently non-contrast techniques to detect infarction have been described. The use of techniques to define myocardial edema, [ 164 166 ] myocardium at risk, [ 167 ] myocardial hemorrhage, and microvascular obstruction, [ 168 ] has also grown greatly.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…Echocardiography was therefore more sensitive to detect acute versus chronic infarctions. Undetected myocardial infarctions were smaller, less extensive and less transmural, associated with non-anterior localization and higher ejection fraction as compared to detected myocardial infarctions [ 133 ].…”
Section: Acute and Chronic Coronary Artery Diseasementioning
confidence: 99%